KERJA SAMA ORANG TUA DAN GURU DALAM MENGEMBANGKAN IMAN SISWA KELAS VIII DI SMPN 2 NGENYAN ASA KABUPATEN KUTAI BARAT TAHUN PEMBELAJARAN 2020/2021 - Rusdi Rusdi; Paulina Maria Ekasari Wahyuningrum; Silvester Adinuhgra (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2021)
This study aims to describe the cooperation of parents and teachers in developing students' faith in Ngenyan Asa Junior High School 2, West Kutai Regency in the Academic Year of 2020/2021. Through this study, collaboration between parents and teachers is one way to develop students' faith. This research is also to look further into the forms of cooperation carried out by parents and teachers and to describe the obstacles experienced by teachers and parents in developing students' faith. The type of research used is descriptive research with a qualitative approach. Data were obtained by using interview and documentation methods. The research informants were 20 people. They are one principal, one Catholic religion teacher, nine students in grade VIII and nine parents of the students. The data analysis technique used is the Miles and Huberman technique which has three steps such as data reduction, data presentation, and conclusions.